Differences in nutritional status of exclusively breastfed and non-exclusively breastfed infants aged 0-6 months in Kutambaru Village, Munte Subdistrict - Tarigan, Denada Br; Sibagariang, Eva Ellya; Ginting, Rapael; Halim, Binarwan; Kuswani, Lili; Silaen, Mangatas; Hutapea, Johnson; Iskandar, Dalmy; Nasution, Syamsul Arifin (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Nutritional status in children under five remains a critical public health issue in Indonesia, characterized by high rates of stunting (21.6%) and wasting (7.9% in North Sumatra). Exclusive breastfeeding (EBF) for the first six months is vital for optimal growth, but compliance is low. This study aimed to analyze the determinants of nutritional status, focusing on the differences between infants aged 0-6 months receiving exclusive breastfeeding and those receiving breastfeeding plus early complementary feeding (MPASI). This research employed a comparative analytical design with a total sampling of 40 mothers and their infants (0-6 months) in Kutambaru Village, Munte Subdistrict. The independent variables were breastfeeding status (exclusive vs. non-exclusive) and complementary feeding status. The dependent variable was infant nutritional status (weight-for-length). Data were analyzed using the Chi-Square test. The results demonstrated a statistically significant association between exclusive breastfeeding and infant nutritional status (p = 0.019). Infants who received EBF were significantly more likely to have an optimal nutritional status. Complementary feeding also showed a significant association (p = 0.033). In conclusion, exclusive breastfeeding is the dominant factor significantly associated with optimal nutritional status in infants 0-6 months. Strengthening interventions to promote EBF is critical to prevent malnutrition.